The Correlation between Vocabulary Mastery and Reading Comprehension of Students' at the Eleventh Grade of SMA Negeri 1 Palu - Andi Ardini; Mochtar Marhum; Muhammad Arid; Jamiluddin Jamiluddin (Hasanuddin University, 2025)
The ability to understand and evaluate written information is known as reading comprehension, while vocabulary mastery is the ability to use words in a language effectively. This study looked at how reading comprehension and vocabulary mastery relate to one another among eleventh-grade students at SMA Negeri 1 Palu. Out of a total population of 534 students in 15 courses, 73 individuals were chosen at random to participate in a correlational study design. Multiple-choice exams with 30 questions for reading comprehension and 50 items for vocabulary mastery were used to gather data. A linearity test, Spearman's rank correlation, and the Kolmogorov–Smirnov test for normalcy were used to analyse the data because of its non-normal distribution. The findings showed a p-value of 0.135 (p > 0.05), indicating no significant relationship between reading comprehension and vocabulary competence. A very little positive link was shown by the correlation coefficient (rs = 0.177). Therefore, it can be said that in this particular situation, students' reading comprehension ability is not strongly predicted by vocabulary competence alone.